"Things begin to speak by themselves": Pierre Schaeffer's myth of the seashell and the epistemology of sound. Issue 1 (2nd January 2021) - Campbell, Iain
ABSTRACT: This paper considers the role of myth and phenomenology in Pierre Schaeffer's research into music and sound, and argues that engagement with these themes allows us to rethink the legacy and contemporary value of Schaeffer's thought in sound studies. In light of critique of Schaeffer's project, in particular that developed by Brian Kane and Schaeffer's own apparent self-disavowal, this paper returns to Schaeffer's early remarks on the "myth of the seashell" in order to examine the conditions of this critique. While Kane argues that Schaeffer's recourse to myth, coupled with his adoption of Husserlian phenomenology, leads to a closure of his inquiry and a failure to accommodate the contingency of his position, this paper argues that Schaeffer's myth of the seashell brings into focus an open-ended, motivating phenomenological problem concerning subjectivity and objectivity that runs through his thought. Drawing on the philosophical work of Gaston Bachelard and Gilles Deleuze, this paper considers the epistemological significance of this moment in Schaeffer's thought, suggesting a "problematic" account of the myth of the seashell that puts Schaeffer into conversation with contemporary work in epistemology.